OPTIMALISASI PEMBERDAYAAN MITRA SB GALLERY: STRATEGI PENINGKATAN KELEMBAGAAN DAN PEMASARAN UMKM KERAJINAN REOG PONOROGO - Umi Isnatin; Lutfy Ditya Cahyanti; Bambang Setyo Utomo; Aziz Mustafa (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
This study aims to analyze the impact of the SB Gallery partnership empowerment program on institutional strengthening and marketing strategies for MSMEs in Reog Ponorogo crafts. The methods employed include training, mentoring, and providing tools and raw materials. The results indicate that the program successfully improved business management quality, product standards, and expanded market reach through digital platforms. With continued support, SB Gallery is expected to make a greater contribution to the preservation of Reog art and the growth of the creative economy in Ponorogo.